A REVIEW ON PHYTOCHEMICAL AND PHARMACOLOGICAL SIGNIFICANCE OF CANTHIUM PARVIFLORUM LAM - Kala, Sirigiri Chandra (International Journal of Current Pharmaceutical Research, 2016)
A large number of medicinal plants are explored from the natural flora for production of commercial drugs. Approximately 20% of the plants found in the world have been submitted to pharmacological or biological tests. Canthium parviflorum is an important medicinal plant used in indigenous system of medicine in India and abroad. To isolate and characterize biologically active molecules, many medicinal plants were screened. Though the medicinal importance of this plant is known, but the potential source of this plant for biologically active molecules is not known. So, the present review on Canthium parviflorum is opens a gateway to find out useful and novel drugs.